Evaluating and Selecting Employees for Undertaking and Implementing New Projects - Michał SĄSIADEK; Waldemar WOŹNIAK; Marek KLIMENT (Communications of International Proceedings, 2023)
This paper presents the issue of selecting people for effective, multi-disciplinary working teams. We describe how to create working teams that are best suited to work in the three departments of the enterprise analysed, on the basis of a real-life example. The selection of the right people to carry out the tasks assigned to them, is a key element in achieving success in any project.
Keywords: Myers Briggs Type Indicator (MBTI); personnel management; evaluation